Development and Evaluation of a Novel Buccal Dosage Form of Ketamine - Jahan, Fatima (Curtin University, 2022)
Widespread therapeutic use of ketamine is limited by adverse effects and poor oral bioavailability, therefore improved formulations are required. In this project, mucoadhesive and orally disintegrating buccal films containing plain ketamine or ketamine-loaded microparticles were developed and characterised. Pharmacokinetic properties of optimized films were compared against ketamine oral solution and sublingual lozenges in rabbits. Results showed that buccal films may be preferable in pain management, due to enhanced bioavailability and sustained ketamine absorption.